Flow determination of an intravenous fluid delivery system for large animals - Nascimento, Ana Victória Zeppelini (2009)
Intravenous (IV) administration of fluids is largely practiced in veterinary medicine. For this purpose, a sterile IV set and a large fluid container are required to assure a safe and efficient infusion. Once the IV set has been developed, fluid flow determinations must be established in order to assure the amount of fluid to be delivered to a given animal in a given time. The purpose of this study was to determine the flow of water through an IV set designed specifically for large animals with the flow clamp in a full open position. The flow rate achieved was 7,32 l/h.